2020
DOI: 10.20448/journal.507.2020.51.1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Population Growth on Disaggregate Energy Generation Source from (Hydro Power, Natural Gas, Oil and Coal Source) in Nigeria

Abstract: This research tries to investigate the impact of population growth on energy generation in Nigeria using Auto Regressive Distributive Lag (ARDL). The study employed an econometric methodology involving the use of unit root test, cointegration test technique. The study use of different source of electricity production in Nigeria such as hydro power source (HPS), natural gas source (NGS), oil and coal sources (OCS) , as dependents variables which were regress against population and real gross domestic product (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Also in Pakistan Meo et al (2018) apply ARDL bound test found that there is asymmetries relationship between inflation, unemployment and poverty. Bala, Ayatu, and Maijamaa (2020) and Mansoor (2018) found that population growth has direct impact on energy generation and demand in Nigeria and Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also in Pakistan Meo et al (2018) apply ARDL bound test found that there is asymmetries relationship between inflation, unemployment and poverty. Bala, Ayatu, and Maijamaa (2020) and Mansoor (2018) found that population growth has direct impact on energy generation and demand in Nigeria and Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The hydrogen conversion rate against the different fuels can be considered for assessment, as shown in Table 8. These values only are considered for input as raw material, and the other costs as described in the above sections be accounted for to compute per kg cost of Hydrogen (Bala et al, 2020;Kang et al, 2014).…”
Section: Hydrogen Conversion Rate From Different Fuelsmentioning
confidence: 99%